PREVALENCE OF THE DISEASES OF OSTEOMUSCULAR SYSTEM AND FRACTURES AMONG THE PERSONS OF YOUNG AGE IN IRKUTSK - L. S. Dats (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The purpose of a research was the study of the frequency of arthralgia, prevalence of the diseases of osteomuscular system, and fractures among the persons from 14 to 24 years in Irkutsk. The frequency of arthralgia composed. 22,4 %. The prevalence of the diseases of osteomuscular system composed. 36561 to 100000. Fractures occurred in 23,8 % people at the age of up to 24 years.